Responding Effectively to Women Experiencing Severe Abuse: Identifying Key Components of a British Advocacy Intervention. (January 2016) - Howarth, Emma; Robinson, Amanda
This article presents key findings from a multisite evaluation of Independent Domestic Violence Advisor (IDVA) services—a form of intervention targeted specifically at women experiencing severe domestic abuse. Results highlight the complex lives of women accessing these services and the efforts of IDVAs to connect women with multiple community resources. Women remaining engaged with services reported positive safety outcomes. Frequency of contact with an IDVA and the number of community resources accessed were positively associated with the odds of achieving safety. These findings suggest this intervention is a promising strategy for tackling severe and complex cases of domestic abuse.